Guidelines for Organizing Off-site Activities to Enhance Knowledge of Western Music History in Thailand - Mongkonchat, Chananya; Laovanich, Monsikarn (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2025)
This article presents guidelines for organizing off-site activities to enhance the learning of Western music history within the Thai context. The study has three primary objectives: 1. to propose concrete approaches for conducting off-site learning activities; 2. to strengthen educators’ planning and instructional management skills for off-site learning; and 3. to develop undergraduate music students’ knowledge of Western music history through experiential learning. The primary target group comprises undergraduate students majoring in music disciplines. The research methodology involved analyzing historical documents on Western music to identify key topics relevant for student learning and surveying significant sites in Thailand—such as museums, theaters, and cultural institutions—to assess their suitability and potential for integration into off-site educational activities. The findings indicate that off-site activities are an essential tool for enriching knowledge and providing holistic learning experiences. Key outcomes include: 1. identification of important locations and resources related to Western music history in Thailand; 2. recommendations for adaptable teaching strategies for off-site learning; 3. development of systematic planning and implementation methods; and 4. formulation of effective strategies for summarizing and evaluating learning outcomes to support higher education objectives. This study underscores the importance of off-site activities in facilitating deeper understanding, bridging theoretical knowledge with real-world experience, and offering practical guidance for educators to enhance instructional practices in response to the needs of 21st-century learners.